MR Imaging of the Pituitary Gland and Postsphenoid Ossification in Fetal Specimens - Mehemed, T.M.; Fushimi, Y.; Okada, T.; Kanagaki, M.; Yamamoto, A.; Okada, T.; Takakuwa, T.; Yamada, S.; Togashi, K. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: A thorough knowledge of fetal growth and development is key to understanding both the normal and abnormal fetal MR imaging findings. We investigated the size and signal intensity of the normal pituitary gland and the intrasphenoidal ossification around the Rathke pouch in formalin-fixed fetuses on MR imaging.MATERIALS AND METHODS: Thirty-two fetuses with undamaged brains were included in this study (mean age, 19.93 weeks; age range, 12–31 weeks). Visual inspection of the pituitary and ossification around the Rathke pouch in the sphenoid bone or the postsphenoid ossification was conducted. The extent of pituitary and postsphenoid ossification, pituitary/pons signal ratio, and postsphenoidal ossification/sphenoid bone signal ratio was compared according to gestational age.RESULTS: The pituitary gland was identified as a hyperintense intrasellar structure in all cases, and postsphenoid ossification was identified as an intrasphenoidal hyperintense area in 27 of the 32 cases (84%). The mean pituitary/pons signal ratio was 1.13 ± 0.18 and correlated weakly with gestational age (R2 = 0.243), while the mean postsphenoid ossification/sphenoid bone signal ratio was 2.14 ± 0.56 and did not show any increase with gestational age (R2 = 0.05). No apparent change in the size of pituitary hyperintensity was seen with gestational age (R2 = 0.001). Postsphenoid ossification showed an increase in size with gestational age (R2 = 0.307).CONCLUSIONS: The fetal pituitary gland was hyperintense on T1-weighted images and the pituitary/pons ratio and extent of postsphenoid ossification correlated weakly with gestational age.SPsphenoid bone